ESSENCE AND MAIN TASKS OF PROJECT LOGISTICS - Русанова, Светлана (SWorldJournal, 2020)
Most projects involve the creation of new facilities (eg construction projects, infrastructure projects) or the development of existing facilities (eg reconstruction projects), which are the essence of the project products. Many projects include logistic